Tomáš Halík's Vision of Christianity - Jasiński, Karol (Studia Warmińskie, 2024)
The main purpose of the paper, which a point of reference are the relevant works of the Czech philosopher and theologian Tomáš Halík, is to critically present his vision of Christianity. Its essential element is to describe it primarily by the biblical metaphor of 'the way', i.e. a path of wandering, seeking and following, rather than as an organised religion expressed in institution and cult. Halík thus postulates the need to move from the Christianitas civilisation to a Christianity as a way of human spiritual development and from an ideologised and closed Catholicism to a catholicity open to cultural and religious dialogue. He also points to the need to value a different type of theology in Christianity, which should be less rationalist and more hermeneutic.